Perampanel in the additional therapy of focal and primary generalized tonic-clonic seizures in children 4–12 years old: clinical data, experience of use and practical recommendations - K. Yu. Mukhin; E. D. Belousova; S. G. Burd; M. V. Barkhatov; N. A. Ermolenko; S. K. Zyryanov; E. I. Karpovich; E. A. Morozova; G. V. Odintsova (Эпилепсия и пароксизмальные состояния, 2021)
On March 18, 2021, an online council of experts in the field of epilepsy treatment was held, dedicated to the use of perampanel in the additional therapy of focal seizures (FS) and primary generalized tonic-clonic seizures (PGTCS) in children 4–12 years old. During the event, the features of the use of perampanel in this group of patients were discussed, considering the specifics of everyday clinical practice, current possibilities of PGTCS and FS therapy in children, its goals, as well as unsolved problems in the treatment of pediatric patients with PGTCS and FS. Particular attention was paid to the role of perampanel in the treatment of PGTCS and FS in children and its effectiveness in specific types of focal seizures.